2020
DOI: 10.1038/s41598-020-60418-3
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and curing reactions of melamine formaldehyde resin in cells of impregnation-modified wood

Abstract: Wood modification improves the properties of wood as a building material by altering the wood structure on a cellular level. This study investigated how dimensional changes of wood on a macroscopic scale are related to the cellular level chemical changes on the micron level after impregnation modification with melamine formaldehyde (MF) resin under different heat curing conditions. Our results showed that the curing conditions affected the polycondensation reactions and the morphological structure of the MF re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 43 publications
3
40
0
Order By: Relevance
“…Due to the chemical similarity of PEG and the cell wall constituents, observing the interactions between PEG and the wood cell wall nanostructure suffers from similar challenges as studies of the native cell walls. In such situations, highly useful information can be obtained by spatially-resolved spectroscopic methods such as Raman imaging combined with multivariate image analysis 26 . Moreover, combining spectroscopic imaging with scattering methods offers a powerful set of tools for resolving the penetration depth of PEG in the hierarchical structure of wood.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the chemical similarity of PEG and the cell wall constituents, observing the interactions between PEG and the wood cell wall nanostructure suffers from similar challenges as studies of the native cell walls. In such situations, highly useful information can be obtained by spatially-resolved spectroscopic methods such as Raman imaging combined with multivariate image analysis 26 . Moreover, combining spectroscopic imaging with scattering methods offers a powerful set of tools for resolving the penetration depth of PEG in the hierarchical structure of wood.…”
Section: Resultsmentioning
confidence: 99%
“…Wavenumbers outside the region were excluded. Cosmic ray removal, baseline correction and vector normalization were performed as described previously 26 . Principal component analysis was done after mean-centering of the spectra and the first principal component was used to exclude pixels in the cell lumen based on a score value threshold.…”
Section: Methodsmentioning
confidence: 99%
“…Raman microspectroscopy has also been extensively utilized in studying wood chemistry, with typical applications involving the visualization of cellulose and lignin distributions on a cellular and subcellular level in different types of natural and treated samples [9,17]. Raman images have also been used to study the distributions of wood extractives [18] and various wood modification agents [19][20][21].…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…Comparison of the curves of the FTIR spectra indicated that the C=O stretching vibration at 1724 cm −1 disappeared after nano-copper modification, while the C–O stretching vibration of aliphatic C–OH, aliphatic C–O, and methylol C–OH at 1270 cm −1 increased in the modified PF resin curves (green and blue spectra). These changes revealed that the modified PF resin reacted with acetyl groups in the hemicelluloses [ 42 ]. The modified PF resin samples showed a relatively larger ratio at 1600 cm −1 , which was attributed to the enhanced condensation reaction of the methylol in the PF resin in the presence of nano-copper to form methylene (–CH 2 –) [ 42 ].…”
Section: Resultsmentioning
confidence: 99%